Extensional Flow‐Induced Dynamic Phase Transitions in Isotactic Polypropylene. Issue 17 (4th July 2016) - Ju, Jianzhu; Wang, Zhen; Su, Fengmei; Ji, Youxin; Yang, Haoran; Chang, Jiarui; Ali, Sarmad; Li, Xiangyang; Li, Liangbin
Abstract : With a combination of fast extension rheometer and in situ synchrotron radiation ultra‐fast small‐ and wide‐angle X‐ray scattering, flow‐induced crystallization (FIC) of isotactic polypropylene (iPP) is studied at temperatures below and above the melting point of α crystals (Tmα). A flow phase diagram of iPP is constructed in strain rate–temperature space, composing of melt, non‐crystalline shish, α and α&β coexistence regions, based on which the kinetic and dynamic competitions among these four phases are discussed. Above T mα, imposing strong flow reverses thermodynamic stabilities of the disordered melt and the ordered phases, leading to the occurrence of FIC of β and α crystals as a dynamic phase transition. Either increasing temperature or stain rate favors the competiveness of the metastable β over the stable α crystals, which is attributed to kinetic rate rather than thermodynamic stability. The violent competitions among four phases near the boundary of crystal‐melt may frustrate crystallization and result in the non‐crystalline shish winning out. Abstract : A phase diagram based on different flow induced structures of isotactic polypropylene regulated by strain rate and temperature is constructed. β crystal is generated simultaneously with α crystal showing the enhancement of nucleation ability compared to α crystal. The generation of non‐crystalline shish is attributed to frustration effect of violent competitions among all involved four phases.